2022
DOI: 10.1088/2632-072x/ac7e9d
|View full text |Cite
|
Sign up to set email alerts
|

Layered complex networks as fluctuation amplifiers

Abstract: In complex networked systems theory, an important question is how to evaluate the system robustness to external perturbations. With this task in mind, I investigate the propagation of noise in multi-layer networked systems. I find that, for a two layer network, noise originally injected in one layer can be strongly amplified in the other layer, depending on how well-connected are the complex networks in each layer and on how much the eigenmodes of their Laplacian matrices overlap. These results allow to predic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…(4), spatially uncorrelated and white in time noise acting on the first layer x i 's might lead to amplified fluctuations in the second layer y i 's. 1 Indeed, the variance of the degrees of freedom in the first layer is generated by η i 's which are i.i.d. and white in time, and yields 1…”
Section: B Amplification Of the Fluctuationsmentioning
confidence: 99%
See 4 more Smart Citations
“…(4), spatially uncorrelated and white in time noise acting on the first layer x i 's might lead to amplified fluctuations in the second layer y i 's. 1 Indeed, the variance of the degrees of freedom in the first layer is generated by η i 's which are i.i.d. and white in time, and yields 1…”
Section: B Amplification Of the Fluctuationsmentioning
confidence: 99%
“…It was recently shown that noise acting on layer might be strongly amplified in the other layers depending on the network connectivities. 1 Besides being amplified, the noise structure seems to align with the lowest-lying eigenmodes of the network Laplacian. Building on these results, I investigate the first escape time from the initial basin FIG.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations